To kill a troubadour - Walker, Martin, 1947 January 23- (Walker, Martin, 1947 January 23- Bruno series., 2022)
"When a musician's new song hits a political nerve, he finds himself in the crosshairs of Spanish nationalists' ire, and it's up to Bruno to track down an extremist who seems ready to take deadly measures"--